Efektivitas Model Pembelajaran Kooperatif Tipe Jigsaw Dan Student Teams Achievement Divisions (STAD) Ditinjau Dari Keterampilan Kerjasama Pada Mata Pelajaran Matematika Siswa Kelas 5 SD - Dwi Putri Sulistyowati; Suhandi Astuti (Jurnal Karya Pendidikan Matematika, 2020)
The purpose of this study was to determine the significant differences between the Jigsaw learning model and the Student Teams Achievement Divisions (STAD) learning model in terms of cooperative skills in 5th grade mathematics subjects at SD Sudirman Salatiga Cluster. This type of research is quasi experimental research or quasi-experimental research. Data analysis techniques used are descriptive analysis techniques and T-Test statistical analysis. The results of the study using the T-Test, the value of tcount was 3.023 and t table 1.995 with a significance level of 0.002. Because the probability value of 0.002 is less than 0.05, H0 is rejected and Ha is accepted, which means that the cooperative skills using the Jigsaw model are significantly higher than the STAD model in SD Sudirman Salatiga Cluster. This finding is supported by the average posttest score of the Jigsaw class at 77.93 and the average posttest score of the STAD class at 68.41.Keywords: Jigsaw, STAD, Cooperation Skills